ANALISIS PEMBATAS PRODUKTIVITAS LAHAN PADA TANAMAN JERUK DI KECAMATAN JUNREJO KOTA BATU - Mohammad Imam Mashudi; S Soemarno (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Rain is one of the natural phenomena that is needed but reliable if it exceeds the limit. The one in need of rain is agriculture. The expected rainfall is that which corresponds to the air requirements for each plant. Production of oranges in East Java in Junrejo Sub-District, Batu City. The production ofÂ  plants is determined by limiting factors such as topography and climate. The purpose of this study was to analyze the factors of land development with productivity conditions in Junrejo Sub-District, Batu City. Analysis of land-forming factors consisted of three stages, i.e. ground field checks, field data data, and data analysis. Result of the study indicated that productivity of orange was still vulnerable to limiting factors This could be seen from the factors analyzed, namely rainfall, land slope. Precipitation of rainfall in Junrejo district was analyzed using IDRIS software with mathematical method CA_Markov Chain where the transition matrix was compared t0 and t1 (t1 = t0 + T) Overlaid from the 2 data. The time series is needed to manage rainfall starts from 2007 - 2017. For data validation, rainfall data in 2011 is required as validation data for 2027 forecasting.